Sports scholarships – in relation to the act on sport and judicial practice - Rzeszowski, Jakub (Journal of Education, Health and Sport, 2018)
This article characterizes the model of sports scholarships regulated in the Polish law by the act on sport. The term ‘sports scholarship’ and the form of establishing such scholarships have also been explained. Moreover, attention has been drawn to problems of interpretation concerning this matter, which are connected with the correct use of provisions of the law and rich judicial practise of administrative courts. As a conclusion, amounts devoted to finance sports scholarships have been analysed on the basis of the selected resolutions of local government units.